대학 교양수학 교과목에서 수업 방식에 따른 학업성취도와 수업 만족도 비교 연구 - 이중경(Jung-Kyung Lee) (한국콘텐츠학회 논문지, 24(7), 2024)
본 연구는 대면 수업과 비대면 수업, 비대면 수업과 블렌디드 러닝의 학업 성취도와 수업 만족도를 비교·분석하여 향후 수업 설계 및 운영에 관한 시사점을 제공하는데 목적이 있다. 이 연구를 위해 경기도 소재 A대학교의 2020학년도부터 2023학년도까지 선형대수, 전산수학 두 교과목의 수강생들을 연구대상자로 선정하여 중간고사와 기말고사 성적분포에 대해 비교·분석하였고, 각 학년도별 성적의 통계적 검정을 통하여 수업 방식에 따른 차이점을 확인하고자 하였다. 추가적으로, 강의평가의 설문을 통해 수업 방식에 따른 학생들의 만족도를 조사하여 각 수업 방식의 장·단점을 확인하였다. 연구 결과, 비대면 수업과 대면 수업 간에는 성적 분포 차이가 명확하였고, 비대면 수업과 블렌디드 러닝 비교에서는 블렌디드 러닝이 학업성취도와 수업 만족도가 높았다. 마지막으로, 연구 결과를 바탕으로 비대면 수업이 포함된 교양수학 수업의 효율적인 수업방안에 대해 고찰하고 제안한다. This study sought to analyze the academic achievement of college students in the basic general mathematics subject between face-to-face classes and non-face-to-face classes, and between non-face-to-face classes and blended learning. For this study, students in two subjects, linear algebra and computational mathematics, at University A in Gyeonggi-do from 2020 to 2023 were selected as research subjects, and the distribution of midterm and final exam scores were compared and analyzed. We attempted to confirm differences according to teaching methods through statistical testing of grades for each year. Additionally, students' satisfaction with each class method was investigated through a course evaluation survey to identify the pros and cons of each class method. Lastly, based on the research results, we consider and suggest efficient teaching methods for the basic general mathematics classes that include non-face-to-face classes. KCI Citation Count: 0